Body evaluation and body ownership in patients with inflammatory bowel disease: the role of interoceptive sensibility and childhood maltreatment : full length manuscript - Atanasova, Konstantina; Lotter, Tobias; Bekrater-Bodmann, Robin; Kleindienst, Nikolaus; Thomann, Anne K.; Lis, Stefanie; Reindl, Wolfgang (International journal of behavioral medicine, 2024)
Inflammatory bowel diseases (IBD) are accompanied by symptoms that can vastly affect patients’ representations of their bodies. The aim of this study was to investigate alterations in body evaluation and body ownership in IBD and their link to interoceptive sensibility, gastrointestinal-specific anxiety, and history of childhood maltreatment.
Online veröffentlicht: 21. August 2024
Gesehen am 04.11.2024